Trade-offs and reconciling competing demands for water - integrating agriculture into a robust decision-making framework (data) - Knox, Jerry W.; Hess, Tim M.; Morris, Joe; Haro, David (Cranfield University, 2018)
Supporting information for paper from Anglian Water funded Water Resources East project
Keywords: agriculture'; 'Climate Change'; 'modelling'; 'risk'; 'uncertainty'; 'water resources'; 'Hydrology'; 'Natural Resource Management'; 'Surfacewater Hydrology'